2017
DOI: 10.1016/j.brainres.2016.01.019
|View full text |Cite
|
Sign up to set email alerts
|

Synaptic changes in the hippocampus of adolescent female rodents associated with resilience to anxiety and suppression of food restriction-evoked hyperactivity in an animal model for anorexia nervosa

Abstract: Anorexia nervosa is a mental illness that emerges primarily during early adolescence, with mortality rate that is 200 times higher than that of suicide. The illness is characterized by intense fear of gaining weight, heightened anxiety, obstinate food restriction, often accompanied by excessive exercise, in spite of mounting hunger. The illness affects females nine times more often than males, suggesting an endocrine role in its etiology. Its relapse rate exceeds 25%, yet there are no accepted pharmacological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
53
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 54 publications
(58 citation statements)
references
References 119 publications
(168 reference statements)
4
53
1
Order By: Relevance
“…The rise of pre- and postsynaptic NMDARs could facilitate LTP (long-term potentiation), learning, and memory, often associated more with the rise of NR2A-NMDARs than of NR2B-NMDARs (Liu et al 2004; Massey et al 2004). Supporting this prediction, other cohorts of adolescent female rats that underwent identical ABA and food-restriction-alone treatments exhibited faster acquisition of spatial memory, relative to the CON animals, after recovering from ABA for a week (Aoki et al 2016; Chowdhury et al 2014b). Consistent with this idea, individuals diagnosed with AN are often characterized to be perfectionists, high achievers, and goal-oriented (Kaye et al 2009; Bachner-Melman et al 2007; Sundquist et al 2016; Dura and Bornstein 1989; Beals 2004).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…The rise of pre- and postsynaptic NMDARs could facilitate LTP (long-term potentiation), learning, and memory, often associated more with the rise of NR2A-NMDARs than of NR2B-NMDARs (Liu et al 2004; Massey et al 2004). Supporting this prediction, other cohorts of adolescent female rats that underwent identical ABA and food-restriction-alone treatments exhibited faster acquisition of spatial memory, relative to the CON animals, after recovering from ABA for a week (Aoki et al 2016; Chowdhury et al 2014b). Consistent with this idea, individuals diagnosed with AN are often characterized to be perfectionists, high achievers, and goal-oriented (Kaye et al 2009; Bachner-Melman et al 2007; Sundquist et al 2016; Dura and Bornstein 1989; Beals 2004).…”
Section: Discussionmentioning
confidence: 91%
“…When these two environmental factors are applied simultaneously, a rat's voluntary wheel running increases dramatically (Aoki et al 2016). This food-restriction-evoked hyperactivity, termed activity-based anorexia (ABA), has been used as an animal model for AN (Guisinger 2003; Casper et al 2008; Gutierrez 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The dorsal and ventral hippocampus of adolescent females that have undergone ABA exhibit significant morphological and molecular changes (Aoki, Chowdhury, Wable, & Chen, 2017). Ventral hippocampus is crucial for regulating anxiety responses (Bannerman et al, 2003;Jimenez et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Previous work from this lab showed that an animal model of anorexia nervosa, called activity‐based anorexia (ABA), also evokes increased expression of α4βδ‐GABA A Rs at excitatory synapses of stratum radiatum of the dorsal hippocampus of adolescent female rats (Aoki et al, ) and mice (Wable et al, ). ABA is an animal model that captures three hallmarks of anorexia nervosa: elevated anxiety (Wable et al, ), excessive exercise, and voluntary food restriction (reviewed in Aoki et al, ). ABA is induced in animals by combining restricted food access with free access to a running wheel.…”
Section: Introductionmentioning
confidence: 99%